The Effect of Spiritual Intelligence Training on Adaptability, Accountability and Legislation among 14-16 Year-Old Male Students - Firoz Tizro-Toly; Tavakkol Mosazadeh; Reza Kazemi (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objectives: Various solutions have been proposed to improve adaptability, accountability, and legislation among adolescence, one of which is the legitimacy of students. The objective of this study was to determine the effect of spiritual intelligence training on adaptability, accountability and legality among male students aged 14-16 years. Materials and Methods: The present study was a semi-experimental design with pre-test, post-test and control group. The statistical population of the study included all the 700 14-16 year old male students in the city of Talesh in the academic year 2017-18, among whom 108 were selected by random sampling. Data were collected via a questionnaire of accountability, legality and social adjustment. Data analysis was performed using multivariate covariance analysis (MANCOVA) and using SPSS software version 22. Results: The study showed that after the spiritual intelligence training, the mean (SD) lawfulness score increased from 30.1 (6) in the pre-test to 35 (7.2) in the post-test, P<0.001. The mean (SD) accountability score was increased from 52.4 (9.4) to 70.6 (12.3) in the post-test, P<0.01. The mean (SD) social adjustment score increased from 70.2 (11.6) in the pre-test to in 81.1 (15.5) in the post-test, P<0.001. The mean (SD) scores of participants in the control group in the post-test was not significantly different form the pre-test for any of the variables. Conclusion: The study showed that spiritual intelligence training increased the compatibility, accountability and legitimacy of students. DOI: http://doi.org/10.22037/ch.v7i2.25348